2014
DOI: 10.1021/nn502058j
|View full text |Cite
|
Sign up to set email alerts
|

DNA Origami as an In Vivo Drug Delivery Vehicle for Cancer Therapy

Abstract: Many chemotherapeutics used for cancer treatments encounter issues during delivery to tumors in vivo and may have high levels of systemic toxicity due to their nonspecific distribution. Various materials have been explored to fabricate nanoparticles as drug carriers to improve delivery efficiency. However, most of these materials suffer from multiple drawbacks, such as limited biocompatibility and inability to engineer spatially addressable surfaces that can be utilized for multifunctional activity. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
590
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(632 citation statements)
references
References 54 publications
(137 reference statements)
10
590
2
7
Order By: Relevance
“…Jiang et al [31] and Zhang et al [32] managed to deliver doxorubicin -an anticancer drug and a DNA intercalator -into cells in vivo using rod-like DNA origamis or DNA origami triangles as carriers ( Figure 1B). Zhao et al [33] demonstrated a similar system, except that they used a twisted 3D rod as a vehicle, which enabled tunable release of the doxorubicin molecules ( Figure 1B).…”
Section: Towards Dna-based Drug Delivery Vehicles and Advanced Therapmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al [31] and Zhang et al [32] managed to deliver doxorubicin -an anticancer drug and a DNA intercalator -into cells in vivo using rod-like DNA origamis or DNA origami triangles as carriers ( Figure 1B). Zhao et al [33] demonstrated a similar system, except that they used a twisted 3D rod as a vehicle, which enabled tunable release of the doxorubicin molecules ( Figure 1B).…”
Section: Towards Dna-based Drug Delivery Vehicles and Advanced Therapmentioning
confidence: 99%
“…[4]; Copyright (2006) a box with a switchable lid [6], a tetrahedron [5] and a two-state box [7]. (B) DNA origami nanostructures for delivering doxorubicin (DOX) into cancer cells: an under-twisted rod-like shape [33], a straight rod [31] and a triangle [31,32]. (C) DNA structures for small interfering RNA (siRNA) delivery: a cage with cell-targeting ligands (folate or peptide) at the end of the siRNA motifs [37], and a PEGylated folatemodified nanotube [36].…”
Section: Shape-complementarity-based Constructionmentioning
confidence: 99%
“…In agreement with this, the biodistribution analysis shows that the encapsulated DNA origami was primarily in the blood after 2 h and a smaller fraction accumulated in the liver as expected for liposomal delivery. Same year, Zhang and coworkers demonstrated the potential for DNA origami to deliver the chemotherapeutic molecule doxorubicin to tumors in mice [7]. This strategy has been confirmed several times in vitro and plays to the observation that doxorubicin is easily loaded into DNA nanostructures through intercalation.…”
Section: Animal Experimentsmentioning
confidence: 94%
“…Therefore, new methods to probe the structural integrity of DNA nanovehicles in larger animals are needed. The ability of DNA nanovehicles to target tumors appears to depend on their shape [7] and interactions of nanoparticles with complement factors are also shape dependent. Accordingly, future experiments should aim to elucidate this, as it may not only provide valuable insight for DNA nanovehicles, but for drug delivery vehicles in general.…”
Section: Expert Opinionmentioning
confidence: 99%
“…One potential application that has already been explored with DNA origami constructs is as a drug delivery vehicle. Anti-cancer drugs, such as doxorubicin, can be intercalated into DNA origami designs and used to improve drug efficacy in cell culture models [72,73]. DNA crystals may be suitable for similar use, but with the potential of drugs beyond just small molecule intercalators.…”
Section: Future Directions and Applicationsmentioning
confidence: 99%